Uzbekistan Social Assistance Targeting Assessment - World Bank (World Bank, Washington, DC, 2020)
This report presents the results of a diagnostic study on the targeting of social protection programs in Uzbekistan with a specific focus on low-income family allowances. The objective is to determine the extent to which current programs are reaching the poor and can reduce poverty, and consequently to identify ways to improve the current design features and implementation processes. The study is part of the collaboration between the Government of Uzbekistan and the World Bank in improving the effectiveness of social protection. Targeting is the overall process that enables the administration to inform potential beneficiaries through outreach activities, facilitate application procedures, and assess needs and eligibility to finally enroll beneficiaries. Therefore, targeting involves the delicate process of identifying and selecting beneficiaries. Key findings are that: 1) no common standards exist for outreach activities, and 2) there is a need to better define who belongs to the same household and for procedures to impute income, as well as to standardize the way living conditions are assessed and verified. Moreover, one of the main reasons for exclusion errors is the use of caps in budgeting and in the number of beneficiaries at the local level.